2018
DOI: 10.1108/rpj-10-2017-0199
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive flow finishing of FDM printed parts using a sustainable media

Abstract: Purpose The purpose of this paper is to study the integration between fused deposition modeling (FDM) technology and abrasive flow machining process to improve the surface quality of FDM printed parts. FDM process has some limitations in terms of accuracy and surface finish. Hence, post-processing operations are essential to increase the quality of the part. Design/methodology/approach Initially, a sustainable polymer abrasive gel-based media (SPAGM) using natural polymer and natural additives (waste vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 15 publications
1
26
0
1
Order By: Relevance
“…Mali et al (2018) studied and analyzed significant factors affecting the surface finish of 3D printed parts. They used unidirectional abrasive flow machining to enhance the surface finish of 3D printed parts.…”
Section: Studies On Environmental Orientation Of Sustainable Additive Manufacturingmentioning
confidence: 99%
“…Mali et al (2018) studied and analyzed significant factors affecting the surface finish of 3D printed parts. They used unidirectional abrasive flow machining to enhance the surface finish of 3D printed parts.…”
Section: Studies On Environmental Orientation Of Sustainable Additive Manufacturingmentioning
confidence: 99%
“…They concluded that AM process is more sustainable when weight reduction is more than 50 per cent and when use phase is also included in assessment. Mali et al (2018) examined the factors affecting the surface finish of AM printed parts. They used analysis of variance for analyzing the influence of factors on surface finish.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, it does not require clamping of the part and the outcome is less sensitive to FDM parameters. Abrasive flow machining was used to remove the material, in micro/nano level, from the 3D printed objects and smoothen the surface with no effect on the mechanical properties (Mali et al, 2018). Another nanofinishing approach using ball end magnetorheological process could reduce the surface roughness of PLA part from 20 mm to 81 nm.…”
Section: Introductionmentioning
confidence: 99%